Active Learning: Lessons From Women With Type 2 Diabetes in a Walking Program. Issue 4 (August 2019) - Fritschi, Cynthia; Martyn-Nemeth, Pamela; Zhu, Bingqian; Jung Kim, Min
Purpose: The purpose of this study was to explore the experiences and preferences of sedentary women with type 2 diabetes who had recently completed a pilot 12-week supervised treadmill walking study. Methods: A qualitative design was used. Content analysis was used to assess major themes and subthemes embedded within participants' responses to open-ended questions about their experiences of participating in a walking program. Women were recruited from a database of patients willing to be contacted for research studies. Results: Seven inner-city women with type 2 diabetes (71% African American, age 62 ± 4.2 years, A1C 6.8% ± 1.3, years since diagnosis 6.6 ± 3.4 years) completed the postprogram interview. Only 3 of the 7 women had ever received any diabetes education. Four major themes emerged: (1) supportive environment, (2) personal commitment: overcoming ambivalence, (3) learning, and (4) outcomes, and 8 subthemes emerged. A supportive environment (encouraging, person centered, social, and structured) in combination with actively learning about diabetes and self-monitoring the effects of exercise seemed to be associated with personal commitment and confidence in participating in a walking program. Conclusions: Active/experiential learning in a supportive environment may enhance both personal diabetes knowledge and behaviors among women with little diabetes education and low activity levels.